2021
DOI: 10.1038/s41467-021-27408-z
|View full text |Cite
|
Sign up to set email alerts
|

Helicase Q promotes homology-driven DNA double-strand break repair and prevents tandem duplications

Abstract: DNA double-strand breaks are a major threat to cellular survival and genetic integrity. In addition to high fidelity repair, three intrinsically mutagenic DNA break repair routes have been described, i.e. single-strand annealing (SSA), polymerase theta-mediated end-joining (TMEJ) and residual ill-defined microhomology-mediated end-joining (MMEJ) activity. Here, we identify C. elegans Helicase Q (HELQ-1) as being essential for MMEJ as well as for SSA. We also find HELQ-1 to be crucial for the synthesis-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…It is believed that the synthesis-dependent strand annealing (SDSA) is the most relevant subpathway in the repair of IR-induced DSBs by HR. In this final step, the newly synthesized strand anneals with the similarly processed second DNA strand to restore integrity in the molecule, and the process is completed by DNA synthesis and ligation [ 84 , 85 ].…”
Section: Dsb Repair Pathwaysmentioning
confidence: 99%
“…It is believed that the synthesis-dependent strand annealing (SDSA) is the most relevant subpathway in the repair of IR-induced DSBs by HR. In this final step, the newly synthesized strand anneals with the similarly processed second DNA strand to restore integrity in the molecule, and the process is completed by DNA synthesis and ligation [ 84 , 85 ].…”
Section: Dsb Repair Pathwaysmentioning
confidence: 99%
“…Alternatively, HELQ might be crucial for the strand annealing stage of SDSA after the D-loop is unwound. Two recent studies identified a role for C. elegans and mammalian HELQ in annealing complementary ssDNA strands during microhomology-mediated end-joining and homologous recombination [ 43 , 44 ]. Drosophila HELQ has also been implicated in single-strand annealing repair [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with supplementary CNHEJ-mediated repair compensating for the insufficiency of POLQ-dependent ANHEJ ( 12 ). An alternative prospect is that, in the absence of POLQ, substituted repair processes ( 110 ) exploit MH more distant from the ultimate fusion junction to stabilize the ligation and these may have been omitted from our analyses. In contrast, we determined enhanced MH usage at the inter-chromosomal telomere fusions that are also more abundant in POLQ –/– clones.…”
Section: Discussionmentioning
confidence: 99%
“…While appearing incongruous with the supposition that CNHEJ is the prevailing mode of repair at these junctions ( 111 , 112 ), the actual lengths of MH employed at inter-chromosomal fusion junctions were lesser than those at genomic and intra-chromosomal fusion junctions and were further tempered by POLQ deficiency. The discrepancies in MH lengths at POLQ-independent inter-chromosomal compared with genomic and intra-chromosomal fusions (means of 2.37, 4.14 and 6.44 bp, respectively) suggest distinct processing and end-ligation mechanisms propel inter-chromosomal rearrangements, while refuting the likelihood of diversion into repair processes dependent on more extensive MH, such as single-strand annealing ( 107 , 110 , 113 , 114 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation